Respuesta :

Answer:

  1. y = 6x -1
  2. y = 4x +3
  3. y = 3x -6
  4. y = 9x -8
  5. y = -2x +10
  6. y = 3x +1

Step-by-step explanation:

First of all, look at what the values are in the tables. You are looking to see if the x-values are increasing by 1. Except in problems 5 and 6, that is the case. In those problems, the last x-value is not in sequence. (Not a problem.)

Second, look at the differences between y-values. When the change in x is the same, you want the change in y to be the same. If it s, the rule is a linear rule. (That is the case for all of the problems here.)

Since each rule is a linear rule, it can be written in any of several forms. Your final answer may want to be in "slope-intercept" form, which look__s like ...

  y = mx + b . . . . . . slope-intercept form

To get there, you may want to start with "point-slope" form, which can look like ...

  y = (y2 -y1)(x -x1) +y1 . . . . . . when x2=x1 +1

__

Using this second form on these problems gives ...

(1)  y = (11 -5)(x -1) +5

  y = 6x -1 . . . . . . . . . . . simplified to slope-intercept form

__

(2)  y = (15 -11)(x -2) +11

  y = 4x +3 . . . . . . . . . . . simplified to slope-intercept form

__

(3)  y = (6 -3)(x -3) +3

  y = 3x -6 . . . . . . . . . . . simplified to slope-intercept form

__

(4)  y = (19 -10)(x -2) +10

  y = 9x -8 . . . . . . . . . . . simplified to slope-intercept form

__

(5)  y = (14 -16)(x -(-3)) +16

  y = -2x +10 . . . . . . . . . . . simplified to slope-intercept form

__

(6)  This one is a bit tricky, since the x-values in the table are decreasing, not increasing. One way to deal with that is to reverse the first two table entries, so the first one is (x, y) = (-3, -8) and the second one is (-2, -5). Then our formula gives ...

  y = (-5 -(-8))(x -(-3)) -8

  y = 3x +1 . . . . . . . . . . . simplified to slope-intercept form

_____

Comment on the "point-slope" formula

For arbitrary (x, y) pairs, the "two point" form of the equation of a line is ...

  y = (y2 -y1)/(x2 -x1)(x -x1) +y1

In this set of problems, (x2 -x1) = 1 (for all but the last), so we shortened the form to the one we used above:

  y = (y2 -y1)(x -x1) +y1

When the change in x is 1, as for most of these problems, then the change in y is the slope of the line. That is why we called the reduced form here "point-slope" form. It made use of the first point (x1, y1) and the slope (y2 -y1).

This reduced "point-slope" form cannot be used except under the special circumstances that exist for this problem set. (In problem 6, we had to rearrange the problem to create the right circumstances.)